Post-cold war borders reframing political space in Eastern Europe (Routledge is an imprint of the Taylor & Francis Group, an informa business, 2019)
In the aftermath of the Ukraine crises, borders within the wider post-Cold War and post-Soviet context have become a key issue for international relations and public political debate. These borders are frequently viewed in terms of military preparedness and confrontation, but behind armed territorial conflicts there has been a broader shift in the regional balance of power and sovereignty. This book explores border conflicts in the EU's eastern neighbourhood via a detailed focus on state power and sovereignty, set in the context of post-Cold war politics and international relations